Latitudinal gradients in some, but not all, avian life history traits extend into the Arctic. (2nd December 2019) - Martin, Michaela; Drake, Anna; Rock, Christine A.; Green, David J.
Abstract : Latitudinal variation in avian life history strategies is well documented. Clutch size and nest success tend to increase with latitude, whereas longevity and developmental periods have been argued to decrease with latitude. However, these patterns are largely based on interspecific comparisons of species breeding at tropical and temperate latitudes. We compared the life history of Yellow Warblers Setophaga petechia breeding in arctic habitat at the northern extent of their range, in Inuvik, NWT (68°N), Canada,  with those breeding in temperate habitat in Revelstoke, BC (50°N), and use data from 21 populations spanning 0–68°N to evaluate latitudinal trends in life history traits from tropical to arctic habitats. Females breeding in Inuvik laid first clutches that were slightly (although not significantly) larger and had higher nest success, which resulted in higher annual productivity compared with their low‐ latitude counterparts. Apparent adult survival rates were only marginally lower in Inuvik than in Revelstoke, whereas incubation and nestling periods in the arctic were similar to our temperate site. When comparing life history traits across the Yellow Warbler breeding range, we observed increases in clutch sizes and nest success with increasing latitude that appeared to be associated with declines in adult survival, though this relationship was weakened by the addition of our arctic site. We detected more moderate declines in incubation and nestling periods with increasing latitude. As we observed latitudinal variation in some life history traits, but not a consistent transition of traits associated with a shift from a slow to fast life history from tropical to arctic latitudes, our study suggests that the expectation for a general shift in life history traits may be over‐simplified.